Neuroendocrine gastric carcinoma in a young patient - Svorcan Petar; Alimpijević Tamara; Ušaj Slavica; Bojić Danijela; Protić Marjana; Đorđević Jelena; Vrinić Dušica; Krstić Miodrag; Dapčević Branka (Vojnosanitetski Pregled)
Background. Neuroendocrine tumors cover a spectrum of neoplasms showing wide variations in their clinicopathological and pathogenetic features, as well as prognosis. They may develop throughout the whole gastrointestinal tract. Case report. We described a case of gastric neuroendocrine carcinoma in a 29-year-old male. The patient presented with chronic continuous abdominal pain and weight loss over a 6- month period. Preoperative diagnosis, operative findings, histology and immunohistochemistry of the tumor confirmed the diagnosis of the rare neuroendocrine gastric carcinoma, stage T2N1. Conclusion. Case reports of this rare tumor are important, because of the paucity of studies noted in the gastrointestinal literature as a result of poor identification prior to the advent of modern immunohistochemistry. Significance of accurately diagnosing gastrointestinal neuroendocrine tumors is crucial for an appropriate treatment.